Pengaruh Kualitas Pelayanan Elektronik dan Ulasan Pelanggan Online Terhadap Keputusan Pembelian Lazada Melalui Kepercayaan Pada Generasi Z Sidoarjo - Zakiyah, Imamatuz; Novie, Muhafidhah; Muzdalifah, Laily; Violita, Cynthia Eka (Riwayat: Educational Journal of History and Humanities, 2025)
This study examines how Generation Z's purchasing decisions in Sidoarjo are influenced by online customer reviews and electronic service quality, with trust as a mediating variable. Focusing on Generation Z due to their significant population and high e-commerce activity, particularly on Lazada, the research employs a quantitative approach with purposive sampling. Data was collected from 200 respondents who had made purchases on Lazada within the last three months, using structured questionnaires and analyzed with SmartPLS 4.0.The findings reveal that electronic service quality does not directly affect purchasing decisions but significantly impacts trust, which in turn influences decisions. Conversely, online customer reviews positively and significantly affect purchasing decisions, both directly and indirectly through trust. This highlights trust's critical role as a mediator in e-commerce, where consumers rely on perceived reliability and validity.The study concludes that platforms like Lazada should prioritize improving electronic service quality and leveraging positive customer reviews to build trust and boost sales. It supports theories such as the Theory of Planned Behavior (Ajzen, 1985) and Mayer et al.s (1995) trust model, offering practical insights for e-commerce platforms to enhance user experience and attract younger consumers.